Characterisation of mechanical-electrical properties of graphene nanoplatelets filled epoxy as conductive ink in various patterns - Salim, Mohd Azli; Hosnie, Aina Natasha; Masripan, Nor Azmmi; Md. Saad, Adzni; Sudin, Mohd Nizam; Naroh, Azmi; Feng, Dai (Universiti Malaysia Perlis, 2021)
Graphene is one of conductive material that has been studied widely other than silver in the printed electronics industry. This material is considered as “wonder material” which has excellent properties in conducting electricity. Due to these properties advantageous of graphene, a new research study had been conducted regarding the electrical and mechanical properties of Graphene Nanoplatelets (GNPs) conductive ink in various print patterns. The way properties of graphene af ecting the current flow of ink had become one of the objectives of this study with respect to hardness and sheet resistivity ink. On the other hand, this study aimed to determine the most excellent pattern and width that good in conducting electicity. Based on the existing formulation of graphene-based conductive ink, this study combined three dif erent materials which are Graphene Nanoplatelets as a filler, epoxy resin as a binder, and polytheramine as a hardener. Samples of the ink were patterned into four (4) dif erent types, which are a straight-line, zigzag, sinusoidal, and square pattern, and three (3) dif erent widths, which are 1 mm, 2 mm, and 3 mm. In this study, to achieve the objectives, two tests were conducted, which are the sheet resistivity test by using a four-point probe and hardness test by using a nanoindenter. At the end of this study, sample of ink that have low sheet resistivity and high hardness has good properties among others samples and vice versa. Besides that, the best pattern that had the high performance of graphene was determined and discussed. The findings of this study will be used in the future and be very helpful in improving the performance of the existing conductive ink, which can eficiently conduct electricity at a low cost of production